“I’d say I’m fat, I’m not obese”: Obesity normalisation in poor urban South Africa - (:unkn) unknown (My University, 2020)
Objective:In the past decade, South Africa’s obesity epidemic has increased in both children and adults, and being overweight is becoming the norm. Several contributing factors lead to the normalisation of obesity. One of these is the culturally entrenched likeness of larger body sizes or shapes within a milieu of easily accessible unhealthy food and beverages. This qualitative study advances knowledge about the influence of socio-cultural norms and obesogenic environments on weight under estimation and ‘obesity normalisation’ amongst black South Africans living in an urban setting.Design:A theory-based qualitative study used focus group discussions (FGDs) with a semi-structured interview guide. FGDs were transcribed verbatim and analysed thematically using a constant comparison method.Setting:Soweto, Johannesburg, South Africa, is a setting which has undergone rapid urbanisation and nutrition transition with ubiquitous availability of processed and fast-foods.Participants:Adults older than 18 years living in Soweto (n 57).Results:There is a wide misperception about obesity amongst black Africans living in an urban setting in Soweto. Participants who admitted to being fat or overweight did not view themselves as such. This could be attributed to unchanging socio-cultural factors that reinforce the acceptability of bigger bodies and living in obesogenic environment.Conclusions:Without addressing socio-cultural norms that attribute bigger bodies to beauty and wealth, motivating individuals to address weight gain will prove difficult especially for populations living in obesogenic environments. A multi-faceted strategy is required to address obesity in urban South African settings.
Keywords: African Research